Hypercalcemia due to Primary Hepatic Lymphoma - Hsu, Andrew; Gagnier, Michael; Ryer, Elizabeth; Salhab, Mohammed; Rosmarin, Alan G. (Case Reports in Hematology, 2016)
A 65-year-old female with a history of mixed connective tissue disease and pulmonary fibrosis on azathioprine, hydroxychloroquine, and prednisone (osteoporosis on teriparatide) presented with a 1-month history of hypercalcemia. After discontinuation of teriparatide, the patient’s hypercalcemia persisted. Further evaluation revealed primary hepatic lymphoma as the source of her hypercalcemia.